Sarah Bernhardt - Reef, Catherine (Clarion Books, 2020)
Relates a biography of nineteenth century actor and superstar Sarah Bernhardt. Describes her early life, entry into show business, her famous temper, scandalous affairs, and rise to stardom. Includes black-and-white photographs and a timeline.